Hubungan antara Komitmen Organisasional dengan Stres Kerja pada Karyawan Restoran X - Bambang Susilo dan Riang Gumanti (Jurnal Psikologi, 2011)
Objective of this research is to understand the relationship between organizational commitment and work stress among employees of a restaurant. This research is very important since most of workers are suffered stress. In this research, stress is perceived negatively although it also has positive impact. Eighty four employees from a restaurant participated in this research. They are motivated to fill in two scales i.e.the organizational commitment scale and the work stress scale.The hypothesis analysis revealed that there is negative correlation between organizational commitment and work stress (r = -.31). Employees with higher commitment to build the organization tend to have lower work stress. High organizational commitment meant that employees are able to devote their times to build organization.They are enthusiastically to do anything to make better place for working.Therefore they tend to have lower work stress.